Dental Student’s Awareness on Caries Risk Assessment: A Multicentric Study - K. C. Vignesh; Gnanasekaran Felsypremila; M. S. Muthu; A. Muthanandam Santhosh; Rodrigues Steven; Boopathi Kangusamy; Namira Fateen; Devraj Mysore Indira; T. Mughil; Seema Deshmukh; Shivayogi M. Hugar; Pranav Shetye; et al. (Journal of the Scientific Society, 2024)
Background: Caries risk assessment (CRA) plays a major role in formulating and implementing preventive rather than corrective measures for dental caries, thus reducing the overall cost of management. Dental students’ familiarity with CRA is uncertain and, therefore, it is required to develop and implement regular awareness programs for upcoming dentists in dental schools on the importance of CRA. Aim: The aim of this study was to assess the knowledge, attitude, and practice (KAP) of dental students in three different institutions. Materials and Methods: A validated semi-structured 14-item questionnaire was administered through Google Form to third and final-year undergraduate dental students (n = 540) of three dental centers. The questionnaire consists of three domains: KAP. Students who volunteered to participate and completed the Google Forms were included in the study. The replies that were received after 21 days were not evaluated for this study. Results: The overall knowledge score ranged from 35.2% for “poor socioeconomic level reduces the risk of dental caries” to 88.8% for “diet adjustment will minimize the incidence of dental caries.” There was no statistical significance detected in the responses for the attitude and practice categories. Most participants in the attitude and practice categories strongly agreed that treatment of the dental abnormality minimizes future risk (52.2%) and were confident in applying CRA in practice (73.9%). Conclusion: The results of this study reveal that KAP is adequate among undergraduate dental students (UG) in all the three institutions. However, the usage on the CRA tool is limited in dental practice.